Provisioning WSN coverage via minimax based sensor node placement scheme - Zainol Abidin H.; Md Din N. (2023)
Wireless Sensor Network (WSN) which is capable of sensing, storing data, processing data and transmitting data has been widely applied in providing effective surveillance. Optimum sensor node placement in the surveillance area is needed since the number of sensor nodes that can be deployed are limited. The positions of sensor nodes must be able to provide maximum coverage with a longer lifetime. This paper describes an initial stage of an ongoing project. A Sensor node placement technique which is based on the minimax algorithm is proposed where surveillance locations will be monitored by the closest sensor nodes. Performance study has been carried out by evaluating the performance of the minimax scheme in terms of coverage ratio and uniformity. Uniformity is a performance metric that can be used to estimate WSN lifetime. Simulation results show that WSN with higher sensor nodes will provide a higher coverage ratio and more uniformly distributed sensor nodes.